Kajian Pemanfaatan Tumbuhan Obat Oleh Suku Dayak Belangin di Desa Dange Aji Kecamatan Air Besar Kabupaten Landak - Lusiana Lusiana; Gusti Eva Tavita; Yeni Mariani; Fathul Yusro (Fakultas Teknik, 2023)
The Dayak tribe has a close relationship with nature. They are used to using natural resources such as plants for various needs, including as an ingredient in traditional medication. The Dayak Belangin, one of the Kanayatn Dayak sub-tribes in Dange Aji Village, Landak District, is still using medicinal plants to treat illnesses in their community. This research was conducted to document the knowledge of the dayak Belangin people in Dange Aji Village in utilizing plants as traditional medicine. A total of 163 households of the dayak Belangin community in Dange Aji Village were selected by purposive sampling and in-depth interviews to obtain information about the community's knowledge of using plants as medicine. The data obtained were then analyzed using ethnobotanical indices such as use value (UV), family importance value (FIV), informant consensus factor (ICF), and fidelity level (FL). All respondents interviewed used medicinal plants, with in total there are 53 species belonging to 34 plant families. Asteraceae is a plant family with the highest FIV (11.76). Jambu tokal or guava (P. guajava), mabo (Blumea balsamifera), and engkodok (Melastoma candidum) had the highest UV values (0.76; 0.71, and 0.71, respectively). The highest ICF score (1) includes cancer, wounds, urinary stones, rheumatism, gout, allergies, malaria, hypertension, bloody bowel movements, colds, sore eyes, colds, cholesterol, and broken bones. There are 43 plants with the highest FL value (100%). The local knowledge of the dayak Belangin tribe is prized and must be maintained, especially for the benefit of science and the development of new modern medicines.